Lithium ion battery electrolyte and lithium ion battery

CN122968431APending Publication Date: 2026-10-23JIANGSU RELIANCE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611147016.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

但是,依赖单一阻燃机制的配方在实际应用中存在固有瓶颈:仅靠气相灭火作用往往对电芯内部热积累的抑制不足,而仅靠凝聚相成炭或闪点提升又难以快速中断气相链式燃烧反应

Benefits of technology

1、本发明通过设定SFI指数并使其不低于6.0,配方中加入气相自由基捕获(PFPN)、凝聚相成炭与提高闪点(磷酸酯)以及界面稳定与辅助降燃(氟代溶剂)三种阻燃机制的协同,从而有效中断热失控链式燃烧,同时利用加权系数平衡各组分用量,避免单一添加剂过量导致的循环衰减和低温性能劣化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the technical field of lithium ion batteries, in particular to a lithium ion battery electrolyte and a lithium ion battery. The lithium ion battery electrolyte comprises a carbonate main solvent, hexafluorocyclotriphosphazene PFPN, a phosphate cosolvent, a fluorinated solvent, and a synergistic flame-retardant index SFI of the electrolyte components is SFI = x + 0.6y + 0.3z, wherein x wt% is the mass fraction of the hexafluorocyclotriphosphazene PFPN, y wt% is the mass fraction of the phosphate cosolvent, z wt% is the mass fraction of the fluorinated solvent, and SFI >= 6.0. The electrolyte is combined by components and the SFI index, three flame-retardant mechanisms of gas-phase free radical capture, condensed-phase carbon formation, flash point improvement, interface stability and auxiliary flame reduction are synergistically combined, the flame-retardant effect, cycle performance and low-temperature performance are considered, the SFI can be indirectly verified by low-cost methods such as closed flash point and self-extinguishing time, and the threshold of right maintenance evidence is lowered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium-ion battery technology, and in particular to a lithium-ion battery electrolyte and a lithium-ion battery. Background Technology

[0002] To meet the demands for higher energy density in consumer electronics, power tools, and small power applications, lithium-ion batteries increasingly employ high-silicon content anode systems. However, the dramatic volume changes of silicon particles during charging and discharging lead to repeated rupture and reconstruction of the solid electrolyte interface film, resulting in continuous heat accumulation. Simultaneously, the low flash point of conventional carbonate electrolytes makes the cells highly susceptible to thermal runaway and rapid propagation under mechanical abuse or overheating conditions. Therefore, effectively suppressing thermal runaway while improving energy density has become a core requirement that must be addressed in the development of this type of battery.

[0003] To improve electrolyte safety, flame-retardant additives are commonly used in related technologies. Typical approaches include introducing phosphazenes, phosphate esters, or fluorinated compounds, utilizing single mechanisms such as gas-phase free radical capture, charring in the condensed phase, or reduction of flammability to delay or inhibit combustion. However, formulations relying on a single flame-retardant mechanism have inherent bottlenecks in practical applications: gas-phase extinguishing alone is often insufficient to suppress heat accumulation within the battery cell, while charring in the condensed phase or increased flash point alone is insufficient to quickly interrupt the gas-phase chain combustion reaction. Furthermore, the dosage of certain flame-retardant additives used to achieve sufficient flame-retardant effect can significantly negatively impact ionic conductivity, low-temperature performance, and cycle life, making it difficult to reconcile the contradiction between flame-retardant effect and electrochemical performance. Simultaneously, existing flame-retardant electrolytes lack reliable, low-cost methods for quantitatively determining whether flame-retardant components remain effective after long-term use of the battery cell, making life-cycle safety assurance and post-event verification challenging.

[0004] The aforementioned limitations often lead to fires in conventional flame-retardant electrolytes under harsh conditions such as needle penetration in high-energy-density and high-safety battery applications. Alternatively, while increasing additives may suppress thermal runaway, it significantly sacrifices room-temperature cycle retention and low-temperature capacity retention. Therefore, constructing an electrolyte system that achieves synergistic effects of multiple flame-retardant mechanisms without compromising electrochemical performance, and providing a simple and verifiable method for evaluating the flame-retardant efficacy throughout the entire lifecycle of this system, has become an urgent technical challenge. Summary of the Invention

[0005] In view of this, the present invention aims to at least partially solve one of the technical problems in the related art. To this end, the present invention provides a lithium-ion battery electrolyte that combines hexafluorocyclotriphosphazene (PFPN), a phosphate co-solvent, and a fluorinated solvent in the electrolyte, and defines a synergistic flame retardant index (SFI) = x + 0.6y + 0.3z with a requirement that SFI ≥ 6.0. The formulation incorporates the synergistic effects of three flame retardant mechanisms: gas-phase free radical capture, condensed phase charring, and increased flash point, as well as interface stabilization and auxiliary flame reduction. This effectively interrupts thermal runaway chain combustion. Simultaneously, a weighted coefficient is used to balance the dosage of each component, avoiding cycle degradation and low-temperature performance deterioration caused by excessive use of a single additive. Furthermore, SFI can be indirectly verified using low-cost methods such as closed-cup flash point and self-extinguishing time, lowering the threshold for patent infringement evidence.

[0006] To solve the above-mentioned technical problems, the present invention is implemented as follows: In a first aspect, this invention provides a lithium-ion battery electrolyte comprising: a carbonate main solvent; hexafluorocyclotriphosphazene (PFPN); a phosphate co-solvent; and a fluorinated solvent. The synergistic flame retardant index (SFI) of the electrolyte components is defined as: SFI = x + 0.6y + 0.3z, where x wt% is the mass fraction of PFPN, y wt% is the mass fraction of the phosphate co-solvent, z wt% is the mass fraction of the fluorinated solvent, and SFI ≥ 6.0.

[0007] In one embodiment, the mass fraction x wt% of PFPN is 4~15 wt%.

[0008] In one embodiment, the mass fraction y wt% of the phosphate ester co-solvent is 4~10 wt%.

[0009] In one embodiment, the mass fraction z wt% of the fluorinated solvent is 5~12 wt%.

[0010] In one embodiment, the phosphate cosolvent is selected from at least one of triethyl phosphate (TEP) or dimethyl methylphosphonate (DMMP).

[0011] In one embodiment, the fluorinated solvent is selected from at least one of fluoroethylene carbonate (FEC) or hydrofluoroether (HFE).

[0012] In one embodiment, the closed-cup flash point T of the electrolyte f ≥80℃, and the self-extinguishing time per unit mass SET≤15 s / g.

[0013] In one embodiment, after the electrolyte is assembled into a battery and subjected to charge-discharge cycles, the free electrolyte collected after disassembly is analyzed by gas chromatography-mass spectrometry, which can detect characteristic ion fragments of hexafluorocyclotriphosphazene, and the residual concentration of hexafluorocyclotriphosphazene after cycling is not less than 50% of its initial concentration.

[0014] A second aspect of this invention provides a method for preparing a lithium-ion battery electrolyte, comprising: mixing a carbonate main solvent, hexafluorocyclotriphosphazene (PFPN), a phosphate co-solvent, and a fluorinated solvent; wherein the mass fraction x wt% of PFPN is 4-15 wt%, the mass fraction y wt% of the phosphate co-solvent is 4-10 wt%, and the mass fraction z wt% of the fluorinated solvent is 5-12 wt%, and the SFI = x + 0.6y + 0.3z ≥ 6.0 is satisfied, and the closed-cup flash point T of the electrolyte is... f At ≥ 80℃, the self-extinguishing time per unit mass (SET) is ≤ 15 s / g.

[0015] A third aspect of the present invention provides a lithium-ion battery, comprising: the lithium-ion battery electrolyte, negative electrode, positive electrode, and separator described in any one of the preceding embodiments.

[0016] In one embodiment, the lithium-ion battery has a full-tab structure with laser-welded cross-section, and the average effective welding area S of the positive and negative current collectors is... eff mm 2 The synergistic flame retardant index SFI satisfies: SFI×S eff ≥126 (mm 2 •wt%); and / or, the negative electrode active material of the negative electrode sheet contains silicon-carbon composite particles, and the total silicon mass fraction of the negative electrode sheet is 8~20 wt%.

[0017] In one embodiment, the positive electrode active material of the positive electrode sheet includes NCM8-based or NCM9-based high-nickel ternary materials.

[0018] In one embodiment, the laser full-section welding coverage η of the full tab structure of the lithium-ion battery is ≥80%; and / or, the compaction density of the negative electrode sheet is 1.40~1.65 g / cm³. 3 ; and / or, the compaction density of the positive electrode sheet is 3.30~3.55 g / cm³. 3 .

[0019] In one embodiment, the diaphragm is a double-sided alumina ceramic-coated PE diaphragm, with a mechanical thermal shrinkage rate of ≤2% under the condition of 150℃ / 1 h.

[0020] In one embodiment, the cylindrical lithium-ion battery has an outer diameter of 20-22 mm, a total height of 64.5-66 mm, a steel shell inner cavity height of 64-65.5 mm, a cell winding height of 61.5-63 mm, an insulating ring height of 2.0-2.5 mm, and a winding groove depth of 1.4-1.8 mm.

[0021] Implementing the technical solution of the present invention has at least the following beneficial effects: 1. This invention sets the SFI index to be no less than 6.0, and incorporates three flame retardant mechanisms into the formulation: gas phase free radical capture (PFPN), condensed phase char formation and flash point enhancement (phosphate ester), and interface stabilization and auxiliary flame reduction (fluorinated solvent). This effectively interrupts the thermal runaway chain combustion. At the same time, the weighting coefficient is used to balance the amount of each component to avoid the cycle decay and low temperature performance degradation caused by excessive amount of a single additive.

[0022] 2. This invention further ensures that PFPN provides sufficient gas-phase free radical scavenging capability to effectively suppress thermal runaway by limiting the PFPN mass fraction (x wt%) to the range of 4~15 wt%, while avoiding high concentrations of F in PFPN by limiting x wt% to no more than 15 wt%. - Ligand interference Li + Desolvation kinetics lead to a sharp increase in low-temperature internal resistance and accelerated cycle decay; the mass fraction y wt% of the phosphate ester co-solvent is limited to 4~10 wt%, which allows the phosphate ester to sufficiently increase the flash point and promote char formation, and y wt% does not exceed 10 wt% to prevent excessive reduction in low-temperature ionic conductivity due to the weak solvation ability of the phosphate ester; the mass fraction z wt% of the fluorinated solvent is limited to 5~12 wt%, which ensures that the fluorinated solvent forms a stable SEI film and reduces flammability, and the appropriate range avoids a significant negative impact on ionic conductivity; the synergy of these three factors enables the electrolyte to achieve SFI≥6.0 while maintaining high levels of room temperature cycle retention and low-temperature capacity retention.

[0023] 3. This invention selects at least one of triethyl phosphate (TEP) or dimethyl methylphosphonate (DMMP) as the phosphate co-solvent, and at least one of fluoroethylene carbonate (FEC) or hydrofluoroether (HFE) as the fluorinated solvent. TEP and DMMP have high boiling points and strong polarity due to the substitution of C=O double bonds with PO single bonds in their molecular structures. They can effectively raise the closed-cup flash point of the electrolyte to above 80°C and promote the formation of a condensed phase carbonized layer when heated. At the same time, their specific molecular structures have a controllable effect on electrode side reactions under normal charge and discharge voltages. FEC preferentially reduces to form a dense SEI film rich in LiF and polycarbonates during the first lithium insertion, which significantly inhibits repeated SEI rupture caused by the volume expansion of the high-silicon anode. HFE reduces gas phase flammability by utilizing high CF bond energy and low heat of combustion. By selecting these specific substances, the specific implementation path of the synergistic flame retardant mechanism is clear and can be verified in mass production.

[0024] 4. This invention increases T fThe constraints of ≥80℃ and SET≤15 s / g, which can be measured in a low-cost and standardized manner, together with SFI≥6.0, constitute a ternary safety relationship, which forces the electrolyte to have both a high flash point (not easily ignitable vapor) and rapid self-extinguishing ability. This ensures that even if the SFI meets the standard in form, but the components do not actually produce synergy, the electrolyte can still be screened out through physical property indicators. At the same time, both of these indicators can be measured by a closed-cup flash point meter and a simple combustion time method, with extremely low cost per test.

[0025] 5. Set a threshold of ≥50% residual PFPN concentration after cycling to ensure that the gas phase flame retardant component maintains a sufficient concentration reserve throughout the battery's lifespan, avoiding the decline in flame retardant ability due to film formation consumption or decomposition. Use GC-MS instead of expensive methods such as XPS / NMR as a verification means, which only requires analysis of characteristic ion fragments (such as m / z=285) and simple quantification. The cost of a single analysis is only a few hundred yuan, making quality auditing operable and cost-effective.

[0026] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Detailed Implementation

[0027] The present application will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.

[0028] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges or individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0029] In the description of this application, "A and / or B" can include any of the cases of A alone, B alone, or A and B, where A and B are merely examples and can be any technical feature connected by "and / or" in this application.

[0030] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0031] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.

[0032] Unless otherwise specified, all technical features and optional technical features of this invention can be combined to form new technical solutions.

[0033] Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0034] In this application, "carbonate primary solvent" refers to any non-aqueous proton-inert carbonate solvent capable of dissolving lithium salts and providing ion conduction, which constitutes the basic solvent system of the electrolyte. For example, it may include, but is not limited to, one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC), or any combination thereof.

[0035] In this application, "hexafluorocyclotriphosphazene (PFPN)" refers to inorganic phosphazene compounds having the molecular formula (NPF2)3, which act as gas-phase free radical scavengers and release phosphorus-oxygen free radicals during thermal runaway to interrupt the gas-phase combustion chain reaction. For example, it may include industrial-grade hexafluorocyclotriphosphazene or its homologues with the same flame-retardant function; its typical characteristic ionic fragments may cover at least one of m / z = 285, 220, 165, and 100.

[0036] In this application, "phosphate cosolvent" refers to phosphate cosolvents that can increase the flash point of the electrolyte, promote char formation, and have flame-retardant properties through condensation camera mechanism. For example, it may include, but is not limited to, triethyl phosphate (TEP), dimethyl methylphosphonate (DMMP), triphenyl phosphate (TPP), or combinations thereof.

[0037] In this application, "fluorinated solvent" refers to fluorinated organic solvents that utilize high-bond-energy CF bonds to reduce the heat of combustion, improve flammability, and participate in the formation of a stable solid electrolyte interface film rich in LiF on the negative electrode surface. For example, it may include, but is not limited to, fluoroethylene carbonate (FEC), hydrofluoroether (HFE), trifluoroethyl carbonate, or combinations thereof.

[0038] In this application, the term "Synergistic Flame Retardant Index (SFI)" refers to a general term used to quantitatively measure the synergistic effect among multiple flame-retardant components in an electrolyte. For example, this application defines SFI as SFI = x + 0.6y + 0.3z, where x wt%, y wt%, and z wt% are the mass fractions of PFPN, the phosphate ester co-solvent, and the fluorinated solvent, respectively; however, SFI can also be expressed by other functions weighted according to the flame-retardant contributions of the gas-phase-condensed-phase-interface. In this invention, when SFI ≥ 6.0, it indicates that the three flame-retardant mechanisms in the formulation have produced an effective synergistic effect.

[0039] In this application, "closed-cup flash point (T)" f "T" generally refers to the lowest temperature at which a mixture of electrolyte sample vapor and air ignites upon contact with an ignition source under standard closed-cup conditions. For example, it can be determined using a Pensky-Martens closed-cup flash point apparatus according to ASTM D93 standard. In this invention, T is required to be... f ≥80℃.

[0040] In this application, "self-extinguishing time per unit mass (SET)" refers to the time taken for a unit mass of electrolyte to self-extinguish from ignition under standard combustion test conditions. For example, a quantitative amount of electrolyte can be adsorbed onto a glass fiber carrier and ignited, the combustion time recorded with a stopwatch and divided by the sample mass to obtain the SET. In this invention, SET is required to be ≤15 s / g.

[0041] In this application, "gas chromatography-mass spectrometry (GC-MS)" refers to a qualitative and quantitative analytical method that combines gas chromatography separation with mass spectrometry detection for the identification and determination of characteristic ion fragments and their concentrations in electrolytes containing flame-retardant components. For example, an HP-5MS column can be used with a set temperature program to collect fragments in full scan mode with m / z 40~600, and m / z=285 can be used as the characteristic qualitative ion of PFPN.

[0042] In this application, "characteristic ion fragments" refers to fragment ions with a specific mass-to-charge ratio that correspond to the molecular structure of PFPN and can uniquely indicate its presence in GC-MS analysis, such as m / z 285 ([MF)). + ).

[0043] In this application, "the residual concentration of hexafluorocyclotriphosphazene after cycling is not less than 50% of its initial concentration" means that after the battery has completed charge-discharge cycles, the free electrolyte collected from disassembly is quantitatively analyzed by the aforementioned GC-MS, and the obtained PFPN mass fraction X 残 Satisfy X 残 ≥0.5X 初始 .

[0044] Currently, when lithium-ion batteries employ high-energy-density material systems, the safety hazards posed by the flammability of the electrolyte have become a key issue restricting their application. In related technologies, to improve the flame-retardant performance of the electrolyte, a single flame retardant is often added, such as using only phosphazene compounds or only phosphate ester compounds. However, the mechanism of action of a single flame retardant additive has limitations. Phosphazene compounds mainly interrupt the combustion chain reaction in the gas phase through free radical capture, while phosphate ester compounds primarily function by condensing char and raising the flash point. The two cannot form a synergistic flame-retardant effect between the gas and condensed phases in the same system. Furthermore, achieving sufficient flame retardancy often requires increasing the amount of the single flame retardant added. Excessive phosphazene compounds may lead to a decrease in electrolyte ionic conductivity and deterioration of low-temperature performance, while excessive phosphate ester compounds, due to their weak solvation ability, affect lithium-ion migration, resulting in accelerated cycle capacity decay.

[0045] The inventors discovered through research that the contradiction between the flame-retardant performance and electrochemical performance of lithium-ion battery electrolytes stems from the simplistic flame-retardant mechanism, failing to fully utilize the synergistic effects of different flame-retardant components in the gas phase, condensed phase, and electrode / electrolyte interface. Specifically, hexafluorocyclotriphosphazene (PFPN) can release phosphorus-oxygen free radicals through PN bond cleavage in the early stages of thermal runaway, capturing hydrogen and hydroxyl free radicals in the gas phase that sustain combustion, thereby inhibiting flame spread; phosphate co-solvents such as triethyl phosphate or dimethyl methylphosphonate have high boiling and flash points, promoting the formation of a carbonized layer in the condensed phase, isolating oxygen from contact with combustible gases, and increasing the difficulty of igniting the electrolyte; fluorinated solvents such as fluoroethylene carbonate or hydrofluoroether have high CF bond energies and low self-heating combustion, and can participate in the formation of a lithium fluoride-rich solid electrolyte interface film on the negative electrode surface, enhancing interface stability. If only one type of component is relied upon, it is impossible to apply effective intervention at all stages of the combustion chain reaction simultaneously. Furthermore, arbitrary combination makes it difficult to quantitatively control the contribution of each component, which can easily lead to a certain mechanism being too strong or too weak, and still cannot take into account both flame retardant effect and electrochemical performance.

[0046] While there have been attempts to combine multiple flame retardants in related technologies, there is a lack of quantitative synergistic criteria for the contribution of each component, and no indicator system has been established that is directly related to the actual safety performance of the battery and can be verified at low cost. This makes formula optimization dependent on a lot of trial and error, and makes it difficult to conduct effective quality monitoring and infringement evidence afterward.

[0047] Based on the above analysis, this invention provides a lithium-ion battery electrolyte comprising a carbonate main solvent, hexafluorocyclotriphosphazene (PFPN), a phosphate co-solvent, and a fluorinated solvent. The synergistic flame retardant index (SFI) is defined as: SFI = x + 0.6y + 0.3z, where x wt% is the mass fraction of PFPN, y wt% is the mass fraction of the phosphate co-solvent, and z wt% is the mass fraction of the fluorinated solvent, all in mass percentage, and SFI ≥ 6.0 is required. This index integrates the contributions of three mechanisms—gas-phase free radical capture, condensed-phase char formation and flash point enhancement, and interfacial stabilization and auxiliary flame retardancy—through weighted coefficients. When the SFI meets the condition, these three mechanisms form a forced synergy at the formulation level, effectively interrupting thermal runaway chain combustion. Furthermore, this electrolyte formulation can be further refined by limiting the dosage range of each component, selecting specific types of phosphate esters and fluorinated solvents, and combining the closed-cup flash point (T0). f The physical property constraints of ≥80℃ and self-extinguishing time per unit mass SET≤15 s / g ensure the reliability of the flame retardant effect and the maintenance of electrochemical performance from different dimensions.

[0048] Specifically, the present invention adopts the following technical solution: This invention provides a lithium-ion battery electrolyte comprising a carbonate main solvent, hexafluorocyclotriphosphazene (PFPN), a phosphate co-solvent, and a fluorinated solvent. In the electrolyte, PFPN, the phosphate co-solvent, and the fluorinated solvent are used in combination, and a quantifiable flame-retardant system is constructed based on their synergistic effect on the flame-retardant mechanism. Specifically, the inventors of this invention have discovered that during thermal runaway of battery cells, a single flame-retardant additive often only functions in either the gas phase or the condensed phase. The flame-retardant mechanism is singular and contradicts compatibility with electrochemical performance, making it difficult to balance flame-retardant effect with cycle and low-temperature performance. For example, while using large amounts of PFPN alone can provide gas-phase free radical capture capability, high concentrations may lead to accelerated cycle decay and a sharp increase in low-temperature internal resistance; while using phosphate alone can increase flash point and promote char formation, its weak solvation ability reduces low-temperature ionic conductivity; and while using fluorinated solvent alone can optimize the interface and assist in flame reduction, its flame-retardant efficiency is limited. By combining PFPN, phosphate ester co-solvent, and fluorinated solvent in a specific ratio, the synergistic flame retardant index (SFI) of the electrolyte components is defined as: SFI = x + 0.6y + 0.3z, where x wt% is the mass fraction of hexafluorocyclotriphosphazene (PFPN), y wt% is the mass fraction of the phosphate ester co-solvent, and z wt% is the mass fraction of the fluorinated solvent, with SFI ≥ 6.0. An SFI ≥ 6.0 can forcibly integrate three mechanisms at the molecular level: gas-phase free radical capture, condensed-phase char formation and flash point enhancement, and interfacial stabilization and assisted flame reduction, thereby achieving synergistic flame retardancy. Furthermore, by balancing the dosage range of each component through this weighting coefficient, the electrochemical performance degradation caused by excessive addition of a single component for the sake of a single flame retardant index can be avoided.

[0049] The weighting coefficients in the Synergistic Flame Retardant Index (SFI) were determined as follows: First, the mass loss rate of PFPN, triethyl phosphate, and fluoroethylene carbonate at the thermal runaway characteristic temperature (150–250 °C) and the amount of PO· radicals generated were measured by differential scanning calorimetry-thermogravimetric analysis (TG-DSC) (indirectly calibrated by electron paramagnetic resonance (EPR)) and standardized to PFPN equivalents. Second, the linear fitting slope of the marginal contribution of each component to the SFI was obtained through single-cell limiting oxygen index (LOI) testing and cause-wise regression of the entire cell after needle penetration. Multiple verification experiments with different formulations (each component dosage covering 0–20 wt%) were repeated, and the final convergence yielded a weighting coefficient of x + 0.6y + 0.3z. To achieve the best trade-off between safety and low-temperature performance, the lower limit of the SFI was determined to be 6.0. The fitting process and original data can be found in Table 1.

[0050] Table 1. Validation data for SFI weighting coefficients Note: Normalized flame retardancy contribution is expressed as LOI increase and T f The weighted comprehensive characterization of the increase and decrease in SET was performed. Through fitting multiple sets of formulation experimental data (each component dosage covering 0~20 wt%), the marginal flame retardant contribution slope ratios of PFPN, phosphate ester, and fluorinated solvent converged to 1:0.6:0.3; therefore, the weighting coefficients were set to 1, 0.6, and 0.3, respectively. SFI ≥ 6.0 represents the lower limit threshold for the optimal trade-off between safety and low-temperature performance.

[0051] In one embodiment of the present invention, a method for preparing the above-mentioned lithium-ion battery electrolyte is provided. The method includes mixing a carbonate main solvent, hexafluorocyclotriphosphazene (PFPN), a phosphate co-solvent, and a fluorinated solvent. This preparation method is simple, can be completed through conventional physical mixing, requires no complex chemical reaction processes, and is easily scaled up for industrial production.

[0052] In another embodiment, the carbonate main solvent can be EC:DMC:EMC in a volume ratio of 1:1:1; or it can be a combination of EC:PC:DEC and EMC, for example, in a volume ratio of 1:0.5:2:2; This affects the flame retardant synergy index SFI and T of the present invention. f The compliance of SET is not substantially affected, as long as its basic calorific value is not affected. Therefore, the carbonate main solvent applicable to this invention is not limited to those listed in the examples. As long as it meets the basic solvent properties of being non-aqueous and capable of dissolving lithium salts, it can be combined with PFPN, phosphate co-solvents and fluorinated solvents to achieve the flame retardant synergistic effect of this invention.

[0053] In another embodiment of the present invention, a lithium-ion battery is provided, comprising a positive electrode, a negative electrode, a separator, and the aforementioned electrolyte. Specifically, the battery can be a 21650-type all-tab cylindrical lithium-ion battery. The all-tab structure utilizes laser full-section welding to weld the entire effective cross-section of the positive and negative current collectors to the cover plate and the bottom of the casing, eliminating the problem of uneven current density in traditional single-tab structures. Consequently, the battery's DC internal resistance (DCR) can be reduced from approximately 20 mΩ to less than 8 mΩ, enabling more uniform heat generation during high-current fast charging and avoiding localized hot spots, thus reducing the risk of thermal runaway from the heat source. The synergistic flame-retardant electrolyte provided by the present invention, working in conjunction with this low-heat-generating structure, further enhances the intrinsic safety of the battery from both material and structural perspectives.

[0054] The inventors of this invention have discovered that, in order to achieve the above-mentioned synergistic flame retardant mechanism while maintaining good electrochemical performance, the key lies in precisely defining the mass fraction range of each component.

[0055] For hexafluorocyclotriphosphazene (PFPN), its mass fraction (x wt%) in the electrolyte is limited to 4 to 15 wt%. When x wt% is within this range, PFPN provides sufficient gas-phase free radical scavenging capability to effectively suppress thermal runaway. The gas-phase flame retardant mechanism of PFPN lies in the preferential breakage of the P-N bonds in the PFPN molecule during thermal runaway, releasing a large number of phosphorus-oxygen free radicals (PO·, HPO2). These free radicals can efficiently capture active free radicals (such as H·, OH·, O·) in the gas phase, thereby interrupting the combustion chain reaction and playing a role in gas-phase fire extinguishing. When x wt% is below 4 wt%, the concentration of PN groups in the electrolyte available for thermal decomposition to generate PO· free radicals is insufficient, resulting in a significant reduction in gas-phase free radical scavenging capability, leading to a low synergistic flame retardant index (SFI) and an inability to effectively suppress thermal runaway. For example, in the comparative examples, when x wt% was 1.5 wt% or 3.0 wt%, the battery caught fire or experienced ignition propagation during a fully charged nail penetration test. When x wt% exceeded 15 wt%, the high concentration of F⁻ ligands in PFPN slightly inhibited the desolvation kinetics of Li⁺, leading to increased charge transfer resistance at low temperatures, and a sharp drop in capacity retention at -20°C from over 80% to 62.3%. Simultaneously, the excessive participation of high-concentration phosphorus compounds in SEI film formation increased interfacial impedance, resulting in accelerated cycle decay; for example, at x wt% of 20 wt%, the 500-cycle retention dropped from over 85% to 78.1%. Therefore, the mass fraction of PFPN x wt% is selected to be 4 to 15 wt%, and exemplary point values ​​can be 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, or 15 wt%.

[0056] For phosphate ester co-solvents, their mass fraction (y wt%) in the electrolyte is limited to 4 to 10 wt%. Phosphate ester co-solvents primarily function in flame-retardant systems to promote char formation in the condensed phase and increase the flash point of the system. The PO single bond in its molecular structure has high boiling point and strong polarity; when added to the carbonate main solvent, it can significantly increase the closed-cup flash point of the electrolyte from below 30°C to above 80°C. Simultaneously, upon heating, phosphate esters can promote the formation of a dense char layer in the condensed phase. This char layer can isolate combustible gases from oxygen, interrupting the spread of combustion. When y wt% is below 4 wt%, both the flash point enhancement and char formation capabilities are insufficient, failing to meet the T... fThe requirement of ≥80℃ makes it impossible to effectively prevent initial combustion. For example, in the comparative examples, when y wt% is 0 wt% or 3.0 wt%, the closed-cup flash point is below 80℃ or the self-extinguishing time is prolonged, leading to ignition propagation during the needle penetration test. When y wt% exceeds 10 wt%, the relatively weak solvation ability of the phosphate ester cosolvent itself can cause Li + The decrease in transport number leads to a reduction in the low-temperature ionic conductivity of the electrolyte, causing the capacity retention at -20°C to drop from nearly 80% to around 74%. Furthermore, different phosphate cosolvents have varying degrees of influence on low-temperature performance; for example, dimethyl methylphosphonate (DMMP) has a different effect on Li due to its molecular structure. + The interference from solvation is stronger, and its impact on low-temperature performance is greater than that of triethyl phosphate (TEP) at a y wt% of 10 wt%. Therefore, the mass fraction y wt% of the phosphate cosolvent is selected to be between 4 and 10 wt%, with exemplary point values ​​being 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 8.5 wt%, 9 wt%, 9.5 wt%, or 10 wt%.

[0057] For fluorinated solvents, their mass fraction (z wt%) in the electrolyte is limited to 5 to 12 wt%. Fluorinated solvents primarily function to optimize the interface and assist in flame retardation. Their molecular structure contains high-energy CF bonds (485 kJ / mol), far exceeding the bond energy of CH bonds (413 kJ / mol), requiring higher activation energies for breakage and combustion. Therefore, they inherently possess low heat of combustion, effectively reducing the overall flammability of the electrolyte. More importantly, especially when the fluorinated solvent is fluoroethylene carbonate (FEC), its flammability during the initial lithium insertion process at the silicon-carbon anode (approximately 0.7 V vs Li) is significantly reduced. +LiF, a polycarbonate solvent, preferentially undergoes reduction reactions over other carbonate solvents, forming a dense and stable solid electrolyte interphase (SEI) film rich in LiF and polycarbonate components on the negative electrode surface. This SEI film exhibits excellent mechanical flexibility, effectively accommodating the up to 300% volume expansion and contraction of silicon particles during charge-discharge cycles. This inhibits repeated rupture and regeneration of the SEI film, thereby reducing the continuous consumption of active lithium and electrolyte, and significantly improving the battery's cycle life and low-temperature performance. When z wt% is below 5 wt%, a complete and dense interfacial protective film cannot be formed, and the flame retardant effect is insufficient. However, when z wt% is in the range of 5 to 12 wt%, sufficient interfacial stability and flame retardant synergistic effect can be provided. When z wt% is gradually increased within the range of 5 to 10 wt%, the -20°C retention rate can be improved from 77.5% to 80.5%, and the cycle retention rate can be improved from 86.5% to 89.1%. When z wt% exceeds 12 wt%, the use of low-polarity fluorinated solvents such as HFE may slightly reduce the ionic conductivity of the electrolyte due to their low polarity, resulting in a slight decrease in cycle performance. Therefore, the mass fraction z wt% of the fluorinated solvent is selected to be between 5 and 12 wt%, with exemplary values ​​being 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, or 12 wt%.

[0058] To accurately quantify and ensure the synergistic effect of the three components, this invention defines the Synergistic Flame Retardant Index (SFI). The formula for calculating SFI is as follows: SFI = x + 0.6y + 0.3z Where x wt%, y wt%, and z wt% represent the mass fractions (wt%) of PFPN, phosphate ester co-solvent, and fluorinated solvent in the electrolyte, respectively. The weighting coefficients in this formula were determined through fitting multiple sets of experimental data, reflecting the respective contributions of PFPN, phosphate ester co-solvent, and fluorinated solvent in the flame-retardant synergistic system. PFPN, due to its strong gas-phase free radical scavenging ability, is assigned the highest weight of 1, followed by the condensed phase effect of the phosphate ester co-solvent with a weight of 0.6, and the interfacial and auxiliary flame-retardant effect of the fluorinated solvent with a weight of 0.3. This index provides a clear design criterion with a single value, namely, satisfying SFI ≥ 6.0.

[0059] When the SFI ≥ 6.0, the formulation is forced to incorporate the synergy of three flame-retardant mechanisms to ensure effective interruption of thermal runaway chain combustion. Merely meeting the SFI index is insufficient to fully constrain the safety and performance of the electrolyte in practical applications. To construct a more comprehensive and difficult-to-circumvent safety evaluation system, this invention also considers the closed-cup flash point T of the electrolyte. fThe self-extinguishing time per unit mass (SET) is used in conjunction with SFI as a constraint that must be satisfied simultaneously.

[0060] Specifically, the closed-cup flash point T of the electrolyte f It is limited to a temperature of no less than 80°C, i.e., T f ≥ 80℃. The closed-cup flash point characterizes the lowest temperature at which a mixture of flammable vapors emitted by the electrolyte in a confined space will flash upon contact with an ignition source. (The last part, "T," appears to be a typo and can be left as is.) f Limiting the temperature to above 80℃ means that the electrolyte is less likely to produce flammable vapors, reducing the risk of ignition at the source. f The determination can be performed according to ASTM D93 standard using a Pensky-Martens closed-cup flash point apparatus, which is a standardized, low-cost testing method.

[0061] Meanwhile, the self-extinguishing time (SET) per unit mass of electrolyte is limited to no more than 15 s / g, i.e., SET ≤ 15 s / g. SET measures the time required for a unit mass of electrolyte to completely extinguish after the ignition source is removed once ignited. The constraint of SET ≤ 15 s / g forces the electrolyte to have rapid self-extinguishing capability, enabling it to quickly stop burning even if accidentally ignited. SET can be determined using standard combustion methods, requiring no specialized and expensive equipment, resulting in extremely low cost per test.

[0062] These three indicators, namely SFI ≥ 6.0, T f ≥ 80℃ and SET ≤ 15 s / g together constitute a ternary safety relationship. These represent the composition threshold, the flammable vapor risk threshold, and the extinguishing capability threshold, respectively, comprehensively defining the safety boundary of the electrolyte from three different but interrelated dimensions. Its necessity has been verified experimentally; when an electrolyte only meets the SFI (Signal Fibre Index) but fails to meet the flash point and SET, it will still ignite in a nail penetration test. For example, in a comparative example, the electrolyte's SFI was exactly 6.0, but T... f At approximately 72°C and a SET of 18 s / g, ignition was observed approximately 240 seconds after needle puncture. In another comparative example, SFI and T... f The critical threshold was met, but with a SET of 17 s / g, slight fumes appeared approximately 280 seconds after needle puncture, still indicating a potential safety hazard. The determination of these three indicators can be performed using low-cost standard instruments and methods, significantly reducing the difficulty and technical barriers to subsequent patent enforcement.

[0063] Based on meeting the above safety indicators, the specific selection of phosphate ester co-solvents and fluorinated solvents can make the specific implementation path of the synergistic flame retardant mechanism clearer and have mass production verifiability.

[0064] According to one specific embodiment of the present invention, the phosphate co-solvent is at least one of triethyl phosphate (TEP) or dimethyl methylphosphonate (DMMP). In the molecular structures of TEP and DMMP, the P-O single bond replaces the C=O double bond in the carbonate, giving them high boiling points (TEP boiling point 215℃, DMMP boiling point 181℃) and strong polarity. These properties make them less volatile when heated, allowing them to remain in the electrolyte bulk and on the electrode surface, promoting the formation of a stable carbonized layer in the condensed phase. This significantly increases the closed-cup flash point of the electrolyte to above 80℃, while their chemical stability within the normal charge / discharge voltage window is sufficient to avoid severe side reactions on the electrodes.

[0065] According to one specific embodiment of the present invention, the fluorinated solvent is at least one of fluoroethylene carbonate (FEC) or hydrofluoroether (HFE). FEC, as a cyclic fluorocarbonate, preferentially forms a film on the surface of the silicon-carbon anode, generating a dense SEI layer rich in LiF. This SEI layer not only accommodates the volume expansion of silicon and maintains interfacial stability, but also possesses high chemical stability and ion conductivity due to its high inorganic content. HFE, on the other hand, is a chain-like fluoroether whose high CF bond content in its molecule endows it with extremely low heat of combustion, effectively diluting and reducing the overall flammability of the gas phase.

[0066] To ensure that the battery has continuous and effective flame-retardant protection throughout its entire service life, the inventors have proposed for the first time a reverse verification method for verifying the durability of flame-retardant components.

[0067] According to one embodiment of the present invention, after the battery containing the electrolyte of the present invention completes charge-discharge cycles, the free electrolyte collected from the disassembled battery is analyzed by gas chromatography-mass spectrometry (GC-MS). Characteristic ion fragments of PFPN can be detected by GC-MS. In a specific implementation, the disassembled finished battery can be opened in a glove box, and approximately 50 μL of free electrolyte can be collected using a syringe. After dilution with an equal volume of acetonitrile, GC-MS analysis is performed. An HP-5MS column (30 m × 0.25 mm × 0.25 μm) can be used. The temperature program can be 40°C for 2 minutes, then increased to 280°C at a rate of 10°C / min and held for 10 minutes. The mass spectrometer uses full scan mode with a scan range of m / z = 40~600. Using PFPN standard as a qualitative and quantitative reference, its characteristic ion fragments, such as at least one of m / z values ​​of 285, 220, 165, and 100, are selected as the criterion for judgment, where m / z=285 corresponds to [MF]⁺ fragment ions.

[0068] By quantitatively comparing the PFPN concentration in the electrolyte before and after cycling, a threshold can be established: that is, the residual PFPN concentration (X) after cycling. 残The concentration should not be lower than its initial concentration (X). 初始 50% of ), that is, X 残 ≥ 0.5X 初始 This limitation ensures that the key component of gas-phase flame retardancy, PFPN, maintains a sufficient concentration reserve throughout the battery's entire life cycle, preventing flame retardancy degradation due to trace film formation or decomposition during long-term cycling. GC-MS, a widely available and low-cost method with a single analysis cost of only approximately 200 to 800 yuan, significantly reduces the cost and complexity of verifying product compliance with protection limits compared to expensive analytical equipment such as X-ray photoelectron spectroscopy (XPS) or nuclear magnetic resonance (NMR), providing great convenience and operability for rights protection and quality auditing. Its detection limit can reach approximately 0.1 wt%, sufficient to meet the needs of quantitative detection.

[0069] The electrolyte formulations described above are specially formulated to be compatible with specific high-energy-density cell systems, particularly those employing high-silicon anode systems or combined with full-tab structures.

[0070] In a lithium-ion battery provided by this invention, the negative electrode may contain silicon-based materials. The total silicon content in the negative electrode active material (based on the total weight of the negative electrode active material) can be defined in the range of 8 to 20 wt%. Silicon negative electrodes can provide a theoretical specific capacity far exceeding that of graphite (approximately 3579 mAh / g for silicon vs. approximately 372 mAh / g for graphite), thereby significantly improving the volumetric energy density at the battery level. As the silicon content increases from 8 wt% to 20 wt%, the volumetric energy density of the cell can increase from 651 Wh / L to 695 Wh / L. However, the large volumetric changes of silicon particles during lithium insertion and extraction cause repeated rupture and regeneration of the SEI film, accelerating cycle degradation and generating more heat. The inventors of this invention have discovered that the synergistic flame-retardant electrolyte provided by this invention exhibits excellent compatibility with the high-silicon negative electrode system. In particular, the FEC component, which forms a flexible SEI film rich in LiF, can effectively adapt to the volume expansion of silicon, thereby stabilizing the interface. Experimental data show that, under the protection of the aforementioned synergistic flame-retardant electrolyte system, even with a silicon content of 20 wt%, the highest surface temperature T of the battery in the fully charged nail penetration test is [data missing]. max The temperature is only 129℃, and it does not ignite. Meanwhile, the cycle retention rate remains at 82.3% after 500 cycles. When the silicon content exceeds 20 wt%, for example, reaching 25 wt%, excessive expansion of the electrode will exacerbate problems such as uneven electrolyte distribution and concentrated local heat generation within the electrode assembly, causing the cycle retention rate to rapidly drop to 73.1%, while the needle-punched T... max The temperature can also rise to 135°C. Therefore, by controlling the total silicon content of the negative electrode within this range, the high energy density advantage of silicon materials can be leveraged while effectively mitigating the safety and lifespan challenges posed by the electrolyte technology of this invention.

[0071] Furthermore, the combination of the battery and the all-tab structure of this invention generates a nonlinear safety synergistic gain. The cylindrical battery has an outer diameter of 20-22 mm, a total height of 64.5-66 mm, an internal winding height of 61.5-63 mm, an insulating ring with a thickness of 2.0-2.5 mm on the cover side, a steel shell bottom wall thickness of 0.3 mm, and grooves with a depth of 1.4-1.8 mm on the shell. This is a specific specification of 21650 cylindrical battery.

[0072] In this full-tab structure, the current collector end face is fully connected via laser welding. The welding coverage rate η is defined as the percentage of the effective cross-sectional area of ​​the actual welded connection to the theoretical cross-sectional area of ​​the total end face of the tab. In this invention, this full coverage rate η is set to be no less than 80%, i.e., η ≥ 80%. The fundamental change brought about by the full-tab structure is that the current output path changes from a single point to the entire end face, thereby significantly reducing the ohmic internal resistance of the battery. A high welding coverage rate is key to ensuring this advantage. When η ≥ 80%, the battery's DC internal resistance (DCR) can be reduced to an extremely low level of 8.8 to 6.8 mΩ. This reduction in internal resistance means a significant decrease in Joule heat generated inside the battery under the same current.

[0073] The inventors of this invention have discovered a quantitative synergistic effect between the low heat generation structure resulting from low internal resistance and the low flammability of the synergistic flame-retardant electrolyte, which can be achieved through the safety performance product S. eff To describe. Define S eff Let SFI be the effective conductive area at the electrode tab welding joint, the value of which is related to the welding coverage η and the diameter of the battery. The quantitative constraint of the synergistic relationship between the two can be expressed as: SFI × S eff ≥ 126 mm 2 •wt%. This inequality integrates the flame retardancy (SFI) at the material level and the thermal management capability (S) at the structural level. eff When this product meets the requirement, even under extreme needle-punching abuse conditions, the structurally reduced heat generation and the material-suppressed risk of combustion work together to successfully contain the thermal runaway process of the battery cell within a safe threshold. Experimental results validate the effectiveness of this constraint; when SFI meets the requirement but the weld coverage η is only 60% or 70%, SFI×S eff When the product is less than 126, the battery temperature exceeds 150°C and catches fire or smokes during the nail penetration test. However, when η increases to 80% or higher, SFI×S effWith a value of 126 or higher, even if punctured by a needle, the maximum surface temperature of the battery can be controlled below 133°C, preventing any fire. This demonstrates the necessity of jointly constraining and protecting the material system and structural design as a whole.

[0074] The following detailed description of this application is based on specific embodiments, but the implementation and protection of this invention are not limited thereto. The following embodiments are only some embodiments of this application and are not intended to limit this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.

[0075] Example 1 A lithium-ion battery electrolyte comprises a 1 mol / L LiPF6 carbonate main solvent (EC:EMC volume ratio 3:7), 8 wt% hexafluorocyclotriphosphazene (PFPN), 6 wt% triethyl phosphate (TEP), and 8 wt% fluoroethylene carbonate (FEC). The balance is the main solvent and other conventional additives (such as 2 wt% vinylene carbonate (VC) and 0.5 wt% 1,3-propanesulfonic acid lactone (PS)). The electrolyte has a SFI of 8 + 0.6 × 6 + 0.3 × 8 = 14.0, satisfying SFI ≥ 6.0; and a closed-cup flash point T0. f =88 ℃, satisfying T f ≥80℃; self-extinguishing time per unit mass SET=8 s / g, satisfying SET≤15 s / g.

[0076] The lithium-ion battery is a 21650 all-tab cylindrical battery. The negative electrode is a silicon-carbon composite negative electrode with a total silicon mass fraction of 15 wt%, the remainder being artificial graphite. The negative electrode active material layer is coated on an 8 μm copper foil with a compaction density of 1.52 g / cm³. 3 The cathode is a high-nickel ternary cathode material, NCM811 (LiNi). 0.8 Co 0.1 Mn 0.1 The positive electrode active material layer is coated on a 12 μm aluminum foil with a compaction density of 3.40 g / cm³. The separator is a double-sided alumina ceramic-coated PE separator with a mechanical thermal shrinkage rate of ≤2% at 150 ℃ / 1 h. The cell structure parameters are: outer diameter 21 mm, total height 65.1 mm, steel shell inner cavity height 64.8 mm, winding height 62.3 mm, insulation ring thickness (cover side) 2.2 mm, steel shell bottom wall thickness 0.3 mm, and slot depth 1.6 mm.

[0077] The battery adopts a full-tab structure welded by laser across the entire cross-section, with an average effective welding area S of the positive and negative current collectors. eff =9.4 mm2 The welding coverage η = 85%, satisfying SFI×S eff =14.0 × 9.4 = 131.6 mm 2 • wt% ≥ 126 mm 2 ·wt%.

[0078] After formation (3 charge-discharge cycles at 0.1C), the battery underwent 500 cycles at 25 °C and 1C / 1C within the 2.5–4.2V voltage range, achieving a cycle retention rate of 88.5%. At -20 °C and 0.2C discharge, the capacity retention rate was 79.2%. A fully charged needle penetration test (φ5 mm steel needle, speed 20 mm / s, penetrating the cell and holding for 300 s) resulted in the highest surface temperature T of the cell. max At 122 °C, it does not ignite or explode, and its carbon monoxide release is reduced by 38% compared to the reference electrolyte without flame retardant additives. After cycling, the battery was disassembled, and the free electrolyte was collected in a glove box. GC-MS analysis revealed characteristic PFPN ion fragments with m / z values ​​of 285, 220, and 165. The residual PFPN concentration was 82% of the initial concentration, meeting the threshold of not less than 50% of the initial concentration.

[0079] Example 2 group This set of examples is used to verify the effect of changing the amount of PFPN x on the flame retardant and electrochemical performance of the electrolyte. This set of examples is based on Example 1, except that the mass fraction of PFPN x wt% is changed, as detailed below.

[0080] Example 2a: The PFPN dosage was adjusted to x = 4 wt%, TEP remained at 6 wt%, and FEC remained at 8 wt%. At this point, SFI = 4 + 0.6 × 6 + 0.3 × 8 = 10.0, T... f =82 ℃, SET=14 s / g. Test results: 86.3% retention rate after 500 cycles at 25 ℃, 80.1% capacity retention rate at -20 ℃, needle penetration T max =141 ℃, no fire, CO decreases by 31%.

[0081] Example 2b: The PFPN dosage was adjusted to x = 12 wt%, TEP remained at 6 wt%, and FEC remained at 8 wt%. At this point, SFI = 12 + 3.6 + 2.4 = 18.0, T... f =92 ℃, SET=7 s / g. Test results: 85.8% retention rate after 500 cycles at 25 ℃, 76.5% capacity retention rate at -20 ℃, needle penetration T max =108 ℃, no fire, CO decreases by 42%.

[0082] Example 2c: The PFPN dosage is adjusted to x = 15 wt%, TEP is maintained at 6 wt%, and FEC is maintained at 8 wt%. At this time, SFI = 15 + 3.6 + 2.4 = 21.0, T f =95 ℃, SET=6 s / g. Test results: 85.1% retention rate after 500 cycles at 25 ℃, 75.0% capacity retention rate at -20 ℃, needle penetration T max =102 ℃, no fire, CO decreases by 46%.

[0083] Examples 2a to 2b, together with Example 1 (x = 8 wt%), demonstrate that within the range of x = 4–15 wt%, SFI ≥ 6.0, T f The flame retardant performance was satisfactory at ≥80 ℃ and SET≤15 s / g, with no ignition observed during needle penetration tests, and high levels of cycling and low-temperature performance maintained. When x was below 4 wt% (see Comparative Examples 2 and 3), insufficient gas-phase free radical capture led to a decrease in flame retardant effect; when x exceeded 15 wt% (see Comparative Example 4), although flame retardancy was enhanced, low-temperature performance significantly deteriorated. Therefore, the suitable range for x is 4–15 wt%.

[0084] Comparative Example 2, the PFPN dosage was adjusted to x = 1.5 wt%, TEP = 6 wt%, FEC = 8 wt%, SFI = 1.5 + 3.6 + 2.4 = 7.5, T f =90 ℃, SET = 9 s / g. Although SFI and physical properties meet the requirements, the phosphorus oxygen free radicals generated by thermal decomposition are limited due to insufficient PFPN concentration. After needle puncture, ignition is delayed for about 260 s, thermal runaway is severe, and CO release is 100% of the baseline. It can be seen that PFPN below 4 wt% cannot effectively interrupt the gas-phase combustion chain reaction.

[0085] Comparative Example 3: The PFPN dosage was adjusted to x = 3 wt%, SFI = 7.2, and T... f =65 ℃, SET = 30 s / g. At this time, T f The temperature was below 80 ℃ and the SET was exceeded. The ternary restraint was incomplete, and the fire ignited approximately 220 seconds after needle puncture.

[0086] Comparative Example 4: The dosage of PFPN was adjusted to x = 20 wt%, TEP = 6 wt%, FEC = 8 wt%, SFI = 26.0, T f =98 ℃, SET=5 s / g. Although the flame retardancy is sufficient and it does not ignite upon needle penetration, the retention rate after 500 cycles is only 78.1%, and the capacity retention rate at -20 ℃ drops to 62.3%. The inventors of this invention discovered that F in high-concentration PFPN - Ligand interference Li +Desolvation kinetics increase low-temperature internal resistance, while the impedance of the SEI film formed by phosphorus compounds increases, leading to accelerated cycle decay.

[0087] Example 3 Group This set of examples is used to verify the effect of changing the type and amount y of the phosphate ester co-solvent. This set of examples is based on Example 1, except that the type or amount of phosphate ester is changed.

[0088] In Example 3a, the amount of phosphate ester was adjusted to y = 4 wt% (TEP), at which point SFI = 8 + 0.6 × 4 + 0.3 × 8 = 12.8, T f =81 ℃, SET=11 s / g. Test results: 87.2% retention rate at 25 ℃ for 500 cycles, 79.8% retention rate at -20 ℃, needle puncture T max =138 ℃, will not ignite.

[0089] In Example 3b, the amount of phosphate ester was adjusted to y = 8 wt% (TEP), at which point SFI = 8 + 0.6 × 8 + 0.3 × 8 = 15.2, T f =91 ℃, SET=8 s / g. Test results: 87.6% retention rate after 500 cycles at 25 ℃, 77.3% retention rate at -20 ℃, needle puncture T max =116 ℃, will not ignite.

[0090] Example 3c: The phosphate ester type was adjusted to DMMP, with a dosage of y = 10 wt%. At this point, SFI = 8 + 0.6 × 10 + 0.3 × 8 = 16.4, T f =90 ℃, SET = 8 s / g. Test results: Cycle retention rate 85.9%, -20 ℃ retention rate 74.2%, needle puncture T max =119 ℃, will not ignite.

[0091] Examples 3a and 3b, along with Example 1 (y = 6 wt%, TEP), show that within the range of y = 4–10 wt%, both TEP and DMMP can ensure that the electrolyte meets the ternary safety equation and does not ignite. As y increases, the flash point increases significantly, but the weak solvation tendency of phosphate esters reduces the low-temperature ionic conductivity. TEP at 6 wt% balances flame retardancy and low-temperature performance, while DMMP at 10 wt% reduces the low-temperature capacity retention to 74.2%. Therefore, for applications requiring higher low-temperature performance, TEP can be used, but the dosage should not exceed 8 wt%.

[0092] Comparative Example 5: No phosphate ester co-solvent was added to the electrolyte (y = 0), PFPN = 8 wt%, FEC = 8 wt%, SFI = 8 + 0 + 2.4 = 10.4, but T f<30 ℃, SET≥25 s / g. Due to the lack of high-boiling-point phosphate esters to increase the flash point, the electrolyte flash point is too low, and even if the SFI meets the standard, it is still easy to ignite and will quickly ignite after being punctured.

[0093] Example 4 group This set of examples is used to verify the effect of changing the amount z of fluorinated solvent. This set of examples is based on Example 1, except that the amount or type of fluorinated solvent is adjusted.

[0094] Example 4a: The FEC dosage was adjusted to z = 5 wt%, at which point SFI = 8 + 0.6 × 6 + 0.3 × 5 = 13.1, T f =85 ℃, SET=11 s / g. Test results: Cycle retention rate 86.5%, -20 ℃ retention rate 77.5%, needle puncture T max =135℃, will not ignite.

[0095] Example 4b: The FEC dosage was adjusted to z = 10 wt%, at which point SFI = 8 + 3.6 + 3 = 14.6, T f =89 ℃, SET=9 s / g. Test results: Cycle retention rate 89.1%, -20 ℃ retention rate 80.5%, needle puncture T max =120 ℃, will not ignite.

[0096] Example 4c: The fluorinated solvent was changed to hydrofluoroether (HFE), with a dosage of z = 12 wt%. At this point, SFI = 8 + 3.6 + 0.3 × 12 = 15.2, T f =88 ℃, SET=8 s / g. Test results: Cycle retention rate 86.0%, -20 ℃ retention rate 78.2%, needle puncture T max =117 ℃, will not ignite.

[0097] Examples 4a to 4c, together with Example 1 (z = 8 wt%, FEC), demonstrate that within the z range of 5–12 wt%, both FEC and HFE can meet the ternary safety criteria, with no sparks observed during needle penetration. Furthermore, increasing z helps improve interfacial stability, thereby improving cycling and cryogenic performance. FEC exhibits the best overall performance at 8–10 wt%. While the cycling rate decreases slightly when HFE is used, the cryogenic performance remains acceptable.

[0098] Comparative Example 6, with a non-fluorinated solvent (z = 0), PFPN = 8 wt%, TEP = 6 wt%, and SFI = 8 + 3.6 + 0 = 11.6, T fAt 85 °C and SET = 12 s / g, although the SFI and physical properties met the standards, the cycle retention rate dropped to 87.0%, and the -20 °C retention rate dropped to 75.8%. The inventors of this invention discovered that in the absence of high CF bond energy components such as FEC, the electrolyte flammability is relatively high, and a dense SEI film rich in LiF cannot be obtained at the silicon-carbon anode interface, resulting in limited improvement in cycle performance, especially at low temperatures, while slightly increasing the safety risks during use.

[0099] Example 5 group This set of examples is used to verify the impact of the silicon content in the negative electrode on the cell performance and safety. This set of examples follows Example 1, except that the total silicon mass fraction in the negative electrode is changed by adjusting the ratio of silicon-carbon composite particles to artificial graphite, while maintaining the electrolyte SFI = 14.0 and the full tab welding coverage η = 85%. Details are as follows.

[0100] Example 5a: Total silicon content of the negative electrode is 8 wt%, capacity retention is 89.8% after 500 cycles at 25 °C, capacity retention is 80.6% at -20 °C, volumetric energy density is 651 Wh / L, and needle penetration T... max =124 ℃, will not ignite.

[0101] Example 5b: Total silicon content of the negative electrode 12 wt%, cycle retention 88.0%, -20 °C retention 79.5%, volumetric energy density 668 Wh / L, needle penetration T max =126 ℃, will not ignite.

[0102] Example 5c: Total silicon content of the negative electrode 20 wt%, cycle retention 82.3%, -20 °C retention 74.8%, volumetric energy density 695 Wh / L, needle penetration T max =129 ℃, will not ignite.

[0103] It can be seen that within the silicon content range of 8 to 20 wt%, all embodiments meet the requirement of not igniting when needled. As the silicon content increases, the energy density increases and the cycle decay intensifies. However, due to the effective suppression of silicon volume expansion by the FEC film formation in the electrolyte, the performance degradation is still within an acceptable range.

[0104] Comparative Example 1 (reference): The total silicon content of the negative electrode is 5 wt%, the electrolyte has no flame retardant added, and it ignites after >250 s after needle penetration. The CO release is used as the baseline of 100%.

[0105] Comparative Example 1-1 (silicon content 25 wt%) showed that although it did not ignite upon needle penetration, the cycle retention rate dropped to 73.1%, and the -20 °C retention rate was only 65.2%, indicating that electrode expansion led to excessive performance degradation. Therefore, a total silicon content of 8–20 wt% in the negative electrode, combined with this electrolyte, can balance energy density and cycle life.

[0106] Example 6 group This set of examples is used to verify the all-tab welding coverage η and SFI×S. eff The impact of constraints on safety. This set of embodiments follows Example 1, except that the laser welding parameters are adjusted to change the welding coverage η. The electrolyte formulation remains SFI = 14.0, and the negative electrode silicon content is 15 wt%.

[0107] Example 6a, η = 80%, S eff =9.4 mm 2 SFI×S eff =131.6, DCR 10.5 mΩ, cycle retention 86.2%, needle puncture T max =133 ℃, will not ignite.

[0108] Example 6b, η = 90%, S eff =10.4 mm 2 SFI×S eff =145.6, DCR 7.2 mΩ, cycle retention 89.0%, needle puncture T max =115℃, will not ignite.

[0109] Example 6c, η = 95%, S eff =10.9 mm 2 SFI×S eff =152.6, DCR 6.8 mΩ, cycle retention 89.2%, needle puncture T max =112 ℃, will not ignite.

[0110] Comparative Example 7, η = 60%, S eff =7.3 mm 2 SFI×S eff =14.0×7.3=102.2<126, DCR 15.8mΩ, cycle retention 81.5%, needle puncture T max =158 ℃ (>150 ℃), fire starts.

[0111] Comparative Example 8, η = 70%, S eff =8.4 mm 2 SFI×S eff =14.0×8.4=117.6<126, DCR 12.9mΩ, cycle retention rate 83.9%, needle puncture T max =152 ℃ (>150 ℃), slight smoke appears after 300 s, but there is still a safety hazard.

[0112] When η≥80% and SFI×S eff When the value is ≥126, even under a full charge and needle penetration test, the battery...max The temperature did not exceed 150°C, and no fire occurred; however, when SFI×S eff When the value is below 126 or η is insufficient, even with a flame-retardant electrolyte, heat spread cannot be effectively suppressed. The inventors of this invention have discovered that the all-tab structure, through the synergistic effect of low internal resistance and uniform heat generation with the flame-retardant electrolyte, reduces local heat accumulation, which is an important structural condition for achieving high safety.

[0113] The reason for this can be speculated, when SFI×S eff At temperatures below 126°C, although the electrolyte itself possesses a certain flame-retardant capability, insufficient coverage of the entire tab leads to uneven current distribution, causing localized ohmic heat accumulation and the formation of 'hot spots'. This causes the electrolyte temperature in these areas to prematurely exceed the optimal flame-retardant operating window (such as the decomposition temperature of PFPN), thus preventing the effective global release of PO· radicals. Consequently, chain combustion is initiated and spread from these hot spots. Therefore, the lack of synergy between structure and materials directly manifests as thermal runaway.

[0114] Comparative Example 9 is used to verify that only SFI is satisfied but T is not. f In the case of SET, PFPN = 3 wt%, TEP = 3 wt%, FEC = 4 wt%, SFI = 3 + 1.8 + 1.2 = 6.0, but T... f The temperature was approximately 72 ℃ (<80 ℃), and SET = 18 s / g (>15 s / g), indicating that the ternary constraints were not fully satisfied. The fire ignited approximately 240 s after needle puncture, proving that all three relationships are indispensable.

[0115] Comparative Example 10: PFPN = 5 wt%, TEP = 4 wt%, FEC = 5 wt%, SFI = 5 + 2.4 + 1.5 = 8.9, T f The temperature was approximately 80 °C, and the SET (Self-extinguishing time) was 17 s / g (>15 s / g). Although the SFI (Self-extinguishing Fiber) and flash point were met, the SET exceeded the limit. After approximately 280 s of ignition delay following a needle puncture, only slight smoke was observed, indicating a potential safety hazard. This demonstrates that self-extinguishing time, as a constraint, can effectively identify hidden risks caused by insufficient gas-phase flame retardant components.

[0116] Example 7 The procedure was carried out in accordance with Example 1, except that the carbonate main solvent was replaced from an EC:EMC volume ratio of 3:7 to an EC:PC:DEC:EMC volume ratio of 1:0.5:2:2. The electrolyte had a SFI of 8 + 0.6 × 6 + 0.3 × 8 = 14.0, satisfying SFI ≥ 6.0; the closed-cup flash point T... f =86 ℃, satisfying T f≥80 ℃; self-extinguishing time per unit mass SET=10 s / g, satisfying SET≤15 s / g. After 500 cycles at 25 ℃ and 1C / 1C, the battery retains 87.9% of its cycle life; the capacity retention rate at -20 ℃ is 78.5%. In a fully charged nail penetration test, the highest surface temperature of the cell, Tmax=125 ℃, did not ignite or explode. The results indicate that the type of carbonate main solvent, provided it meets the basic properties of being non-aqueous and capable of dissolving lithium salts, has no substantial impact on the safety performance of the flame-retardant synergistic system of this invention.

[0117] Description of experimental testing methods.

[0118] Closed-cup flash point T f The flash point was determined using a Pensky-Martens closed-cup flash point apparatus in accordance with ASTM D93 standard. The test was conducted under an inert atmosphere and repeated three times, with the average value taken.

[0119] Method for determining the self-extinguishing time SET per unit mass: Immerse the glass fiber strip in the electrolyte until saturated, remove it and hang it vertically, ignite it and record the self-extinguishing time t (s) and weigh the mass of residual electrolyte m (g) on ​​the fiber, SET = t / m; Each measurement is repeated ≥5 times, and the relative deviation is ≤5%.

[0120] Cyclic performance test: Using the LAND CT2001A battery test system, at an ambient temperature of 25 ℃±2 ℃, the battery was charged at a constant current of 1C to 4.2V, then switched to constant voltage charging until the current was ≤0.05C, left to rest for 10 minutes, and then discharged at 1C to 2.5V. The discharge capacity of each cycle was recorded, and the capacity retention rate was the ratio of the capacity of the 500th cycle to the capacity of the 5th cycle.

[0121] Low temperature discharge test: After the battery is fully charged at 0.5C at 25 ℃, it is placed in a high and low temperature chamber of -20 ℃±2 ℃ for 4 hours, discharged at 0.2C to 2.5V, and the discharge capacity is recorded and compared with the 25 ℃ reference capacity.

[0122] Needle penetration safety test: A fully charged battery (4.2V) is placed in an environment of 25 ℃±5 ℃. A φ5 mm heat-resistant steel needle is used to penetrate the battery radially through the center at a speed of 20 mm / s, and the needle tip remains stationary for 300 s; the highest temperature T on the surface of the casing is recorded. max Observe whether a fire or thermal runaway occurs; use an online gas analyzer to determine the percentage decrease in CO release relative to the reference electrolyte.

[0123] GC-MS analysis of the finished electrolyte: After cycling, the battery was disassembled in a glove box, and approximately 50 μL of free electrolyte was collected using a syringe. This was diluted with an equal volume of acetonitrile. An HP-5MS column (30 m × 0.25 mm × 0.25 μm) was used. The temperature program was 40 ℃ for 2 min, then increased to 280 ℃ at a rate of 10 ℃ / min and held for 10 min. The mass spectrometry was performed in a full scan (m / z 40–600). The characteristic ion of PFPN was m / z = 285 ([MF)). + At least one of 220, 165, and 100 can be detected; quantification is performed using the external standard method with PFPN standard, with a detection limit of approximately 0.1 wt%, and the residual concentration is expressed as a percentage of the initial concentration.

[0124] The table below summarizes the main parameters and results of each embodiment and comparative example.

[0125] Table 2. Effect of PFPN dosage (x wt%) on key performance (y wt%=6 wt%, z wt%=8 wt% fixed) When the PFPN concentration is below 4 wt% (Comparative Examples 2 and 3), the concentration of PN groups in the electrolyte that can generate PO· radicals through thermal decomposition is insufficient, resulting in weak gas-phase radical capture ability. The synergistic flame retardant index SFI < 6 (without phosphate ester) or the flash point fails to meet the standard, and thermal runaway chain combustion cannot be effectively suppressed. During the needle penetration test, combustible gas continues to be generated and ignites. When x is in the range of 4–15 wt%, the gas-phase fire extinguishing efficiency increases with increasing PFPN concentration, and the needle penetration T... max As the temperature decreased from 141 °C to 102 °C, CO release continued to decline (31% → 46%); however, the cycle performance remained above 85% when x ≤ 15 wt%, because PFPN itself does not participate in the electrode reaction at normal charge and discharge temperatures, and has limited impact on SEI film formation. Once x exceeds 15 wt% (Comparative Example 4, x = 20 wt%), the F⁻ ligands in high-concentration PFPN slightly inhibit Li + Desolvation kinetics showed that the internal resistance increased at low temperatures, and the capacity retention rate dropped sharply to 62.3% at -20 °C. Simultaneously, the high concentration of phosphorus compounds participating in SEI film formation increased interfacial film impedance, leading to accelerated cycle decay (78.1%). Therefore, the optimal range for x is 4–15 wt%, with an optimal value of 8 wt% (Example 1).

[0126] Table 3 Effect of phosphate cosolvent dosage (y wt%) on key performance (x wt%=8 wt%, z wt%=8 wt% fixed) The high boiling point of phosphate ester solvents (TEP boiling point 215 °C, DMMP boiling point 181 °C) is essentially due to the increased intermolecular polarity and significantly lower vapor pressure resulting from the substitution of C=O double bonds by PO single bonds. When y=0 (Comparative Example 5), the electrolyte flash point is <30 °C, and even if the SFI is satisfied, the lack of support from high-boiling-point phosphate esters leads to a Tflash. f If the condition is not met (<80 °C), thermal runaway propagation is inevitable. When y is in the range of 4~10 wt%, T_f increases from 81 °C to 90 °C with increasing y, and SET decreases from 14 s / g to 8 s / g, satisfying all triple safety relationships; however, when y>8 wt%, the weak solvation ability of phosphate esters leads to Li + The migration number decreased, the low-temperature ionic conductivity decreased, and the capacity retention at -20 °C decreased from 79.8% to 74.2%. DMMP (y=10 wt%) had a greater impact on low-temperature performance than TEP because its methyl phosphate structure had a stronger interference with Li⁺ solvation. The optimal overall concentration was TEP 6 wt% (Example 1).

[0127] When y = 3 wt% (Comparative Example 7, x = 8, z = 8 fixed), although SFI = 12.2 meets the requirement of ≥6.0, the amount of phosphate ester used is insufficient, T f The temperature was only 68 °C (<80 °C), and the SET was 22 s / g (>15 s / g). The ternary safety constraint was incomplete. After needle penetration, the flame ignited after about 260 s, indicating that the ability of condensed phase to form carbon and improve flash point was insufficient when y was below 4 wt%.

[0128] Table 4. Effect of fluorinated solvent dosage (z wt%) on key performance (x wt% = 8 wt%, y wt% = 6 wt% fixed) FEC contains one F atom, and the CF bond energy (485 kJ / mol) is much higher than that of the CH bond (413 kJ / mol), requiring a higher activation energy for combustion, effectively reducing flammability; more importantly, FEC achieves high flammability during the first lithium insertion into the silicon-carbon anode (~0.7 V vs Li). +LiF preferentially reduces to form a dense SEI film rich in LiF and polycarbonates, effectively suppressing SEI cracking caused by the volume expansion and contraction of silicon particles. When z wt% increases from 5 wt% to 10 wt%, the -20 ℃ retention rate increases from 77.5% to 80.5% (improved interface kinetics), and the cycle retention rate increases from 86.5% to 89.1% (enhanced SEI stability), which is the factor contributing most to the system's cycle performance. When z=12 wt% (HFE replacement), the low polarity of HFE slightly reduces the electrolyte ionic conductivity, resulting in a slight decrease in cycle performance (86.0%). The optimal overall concentration is 8 wt% FEC (Example 1), and for the highest cycle performance, 10 wt% FEC (Example 4b) can be selected.

[0129] Table 5 Total silicon content of the negative electrode (y Si Impact on key performance High silicon content (y Si ≥8 wt% provides a higher theoretical specific capacity of the negative electrode (silicon ~3579 mAh / g vs graphite 372 mAh / g), significantly improving the cell volumetric energy density (from 651 Wh / L@8% to 695 Wh / L@20%), but the volume expansion effect intensifies with increasing silicon content: y Si At 20 wt%, the cycle retention rate decreased to 82.3% (vs. 88.5% at 15 wt%), due to uneven electrolyte distribution in the electrode assembly caused by electrode expansion, localized pressure on the diaphragm, and non-uniform heat distribution. It is worth noting that under the protection of the above flame-retardant electrolyte system (SFI=14.0), even with y Si =20 wt%, acupuncture T max It only reached 129 ℃ and did not ignite, proving that the synergistic flame retardant system's safety protection effect on the high-silicon system is not affected by silicon content (within the range of 8~20 wt%). Si At <8 wt%, there is no competitive advantage in energy density; Si When the content is >20 wt%, expansion control is difficult and the initial effect is low. The optimal content is 15 wt% (Example 1).

[0130] Table 6. Impact of All-Electrode Tab Weld Coverage (η) on Safety and Performance The core advantage of the all-tab structure lies in its significantly reduced DC internal resistance (DCR). When η increases from 60% to 95%, the DCR decreases from 15.8 mΩ to 6.8 mΩ, a reduction of approximately 57%. Under the same charge and discharge current, the cell's heat generation power P=I 2 ×DCR decreases significantly with decreasing DCR, and heat accumulation slows down. (Acupuncture T) maxThe temperature dropped from 158 ℃ to 112 ℃. When η < 80% (Comparative Examples 9 and 10), the current density at the local electrode welding point was too high, resulting in local hot spots and causing the thermal runaway trigger temperature to be earlier. Even with a flame-retardant electrolyte with SFI ≥ 6.0, the needle-pierced T max It may still exceed the 150 °C threshold (comparative example 9 measured ignition at 158 ​​°C). When η≥80%, SFI×S eff The synergistic constraint of ≥126 was satisfied, and the low heat generation of the all-tab and the synergistic flame-retardant electrolyte jointly ensured the safety of fully charged needle penetration. η=85% (Example 1) is the overall engineering optimal, and η=90% (Example 6b) is the safety performance optimal (T max =115℃) but the process cost is slightly higher.

[0131] The parts of this invention not described in detail are techniques known to those skilled in the art.

[0132] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.

[0133] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A lithium-ion battery electrolyte, characterized in that, Include: Carbonate as the primary solvent; Hexafluorocyclotriphosphazene PFPN; Phosphate co-solvent; Fluorinated solvents; The synergistic flame retardant index (SFI) of the electrolyte components is defined as: SFI = x + 0.6y + 0.3z. In the formula, x wt% is the mass fraction of hexafluorocyclotriphosphazene (PFPN), y wt% is the mass fraction of the phosphate ester cosolvent, z wt% is the mass fraction of the fluorinated solvent, and SFI ≥ 6.

0.

2. The lithium-ion battery electrolyte according to claim 1, characterized in that, The mass fraction (x wt%) of the PFPN is 4~15 wt%; And / or, the mass fraction y wt% of the phosphate cosolvent is 4~10 wt%; And / or, the mass fraction z wt% of the fluorinated solvent is 5~12 wt%.

3. The lithium-ion battery electrolyte according to claim 1 or 2, characterized in that, The phosphate cosolvent is selected from at least one of triethyl phosphate (TEP) or dimethyl methylphosphonate (DMMP). And / or, the fluorinated solvent is selected from at least one of fluoroethylene carbonate (FEC) or hydrofluoroether (HFE).

4. The lithium-ion battery electrolyte according to claim 1 or 2, characterized in that, The closed-cup flash point T of the electrolyte f ≥80℃, and the self-extinguishing time per unit mass SET≤15 s / g.

5. The lithium-ion battery electrolyte according to claim 1 or 2, characterized in that, After the electrolyte is assembled into a battery and cycled at 1C / 1C at 2.5~4.2V for 500 cycles, the free electrolyte collected after disassembly is analyzed by gas chromatography-mass spectrometry. Characteristic ion fragments of hexafluorocyclotriphosphazene can be detected, and the residual concentration of hexafluorocyclotriphosphazene after cycling is not less than 50% of its initial concentration.

6. A method for preparing a lithium-ion battery electrolyte, characterized in that, Mix the carbonate main solvent, hexafluorocyclotriphosphazene PFPN, phosphate co-solvent, and fluorinated solvent; Furthermore, the mass fraction of PFPN (x wt%) should be 4–15 wt%, the mass fraction of the phosphate ester cosolvent (y wt%) should be 4–10 wt%, and the mass fraction of the fluorinated solvent (z wt%) should be 5–12 wt%, while satisfying SFI = x + 0.6y + 0.3z ≥ 6.0, and the closed-cup flash point T of the electrolyte should be... f At ≥ 80℃, the self-extinguishing time per unit mass (SET) is ≤ 15 s / g.

7. A lithium-ion battery, characterized in that, The lithium-ion battery includes the lithium-ion battery electrolyte, negative electrode, positive electrode, and separator as described in any one of claims 1 to 5.

8. The lithium-ion battery according to claim 7, characterized in that, The lithium-ion battery has a full-tab structure with laser full-section welding, and the average effective welding area S of the positive and negative electrode current collectors is... eff mm 2 The synergistic flame retardant index SFI satisfies: SFI × S eff ≥126 (mm 2 •wt%); And / or, the negative electrode active material of the negative electrode sheet comprises silicon-carbon composite particles, and the total silicon mass fraction of the negative electrode sheet is 8~20 wt%; And / or, the positive electrode active material of the positive electrode sheet includes a high-nickel ternary material.

9. The lithium-ion battery according to claim 7 or 8, characterized in that, The laser full-section welding coverage η of the full tab structure of the lithium-ion battery is ≥80%; And / or, the compaction density of the negative electrode sheet is 1.40~1.65 g / cm³. 3 ; And / or, the compaction density of the positive electrode sheet is 3.30~3.55 g / cm³. 3 .

10. The lithium-ion battery according to claim 7 or 8, wherein, The diaphragm is a double-sided alumina ceramic-coated PE diaphragm, and its mechanical thermal shrinkage rate is ≤2% under 150℃ / 1 h conditions; And / or, the cylindrical lithium-ion battery has an outer diameter of 20~22 mm, a total height of 64.5~66 mm, a steel shell inner cavity height of 64~65.5 mm, a cell winding height of 61.5~63 mm, an insulating ring height of 2.0~2.5 mm, and a winding groove depth of 1.4~1.8 mm.